Public-Private Arbitration in Romanian Law - Daniela Cîmpean; Roxana Vornicu; Dacian C. Dragoș (Transylvanian Review of Administrative Sciences, 2021)
The article endeavors to introduce the constitutional and statutory framework for arbitration in Romania, whilst discussing the dilemmatic legislative provisions allowing for public entities to become parties in an arbitration dispute. It includes a discussion of the concept of administrative contracts in Romania and a chronological analysis of the evolution of public-private arbitration under administrative contracts. Some of the landmark Romanian public-private arbitrations under international investment treaties have held the public agenda in recent years and they shape the public debate on arbitration as fit for purpose when it comes to public contracts.